A cohort study to assess risk of cutaneous small vessel vasculitis among users of different oral anticoagulants. Issue 11 (15th August 2022) - Ajao, Adebola; Cosgrove, Austin; Eworuke, Efe; Mohamoud, Mohamed; Zhang, Rongmei; Shapira, Oren; Kolonoski, Joy; Connolly, John G.
Abstract: Purpose: Cutaneous small vessel vasculitis (CSVV) was identified as a safety signal among patients treated with direct oral anticoagulants (DOAC). This study aimed to determine if CSVV risk differed among patients with atrial fibrillation (Afib) who newly initiated warfarin or a DOAC. Methods: We identified enrollees aged ≥21 years diagnosed with Afib who newly initiated rivaroxaban, dabigatran, apixaban, and warfarin in the Sentinel Distributed Database from October 19, 2010 to February 29, 2020. We selected and followed patients who did not have evidence of the following in the 183 days prior to initiating treatment: CSVV diagnosis, dispensing of other study drugs, select autoimmune diseases or autoimmune medications, cancer diagnoses or chemotherapeutic treatment, kidney dialysis or transplant, alternative anticoagulation indications, or an institutional (nursing home, hospice, hospital) stay on the treatment initiation date (index date) until CSVV outcome or pre‐specified censoring. We conducted 1:1 propensity score matching in six comparisons. Results: CSVV incidence rates for DOACs and warfarin ranged from 3.3 to 5.6 per 10 000‐person years in our matched Afib population. The adjusted CSVV hazard ratio (HR) and 95% confidence interval (CI) was 0.94 (0.64, 1.39) for rivaroxaban versus warfarin; 1.17 (0.67, 2.06) for dabigatran vs. warfarin; 0.85 (0.62, 1.16) for apixaban vs. warfarin; 0.86 (0.49, 1.50) for rivaroxaban vs. dabigatran; 0.99 (0.68, 1.45) for rivaroxaban versus apixaban; and 1.70 (0.90, 3.21) for dabigatran versus apixaban. Conclusion: We did not find significant evidence of differential CSVV risk in pair‐wise comparisons of DOACs and warfarin.